2017
DOI: 10.7150/jca.20739
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Peripheral Benzodiazepine Receptor in Patients with Esophageal Squamous Cell Carcinoma

Abstract: Background: The peripheral benzodiazepine receptor (PBR) has previously been reported as an oncogene in prostate, breast and colorectal cancers, but its prognostic value, biological behavior and function in esophageal squamous cell carcinoma (ESCC) has not been investigated.Methods: qRT-PCR, western blotting and immunohistochemistry (IHC) were used to detect PBR expression in ESCC and matched non-cancerous tissues. Based on all of the significantly independent factors, a nomogram was established to predict the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Although gene or protein expression in the PT is often related to lymphatic, distant metastases and prognosis, it has failed to show a similar predictive value in N+ ESCC patients. 33 , 34 Tumor heterogeneity may be part of the reason for this phenomenon. It is now believed that intra-tumor heterogeneity reflects the ongoing linear and branching evolution, resulting in multiple simultaneous subclones that may individually be capable of giving rise to metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Although gene or protein expression in the PT is often related to lymphatic, distant metastases and prognosis, it has failed to show a similar predictive value in N+ ESCC patients. 33 , 34 Tumor heterogeneity may be part of the reason for this phenomenon. It is now believed that intra-tumor heterogeneity reflects the ongoing linear and branching evolution, resulting in multiple simultaneous subclones that may individually be capable of giving rise to metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that TSPO expression is elevated in cancer and correlate with poor survival in glioblastoma (30,31), breast cancer (32,33), prostate cancer (33,34), liver cancer (35,36), colorectal cancer (33,37,38), melanoma (39), and esophageal squamous cell carcinoma (40). However, there is relatively little information on the possible prognostic role of TSPO in HNSCC.…”
Section: Introductionmentioning
confidence: 99%